A cost effectiveness based safety and efficacy study of resterilized intra-parenchymal catheter based intracranial pressure monitoring in developing world - Gupta, Deepak; Bisht, Ajay; Batra, Priyam; Mathur, Purva; Mahapatra, Ashok (Asian Journal of Neurosurgery, 2016)
Background: The management of traumatic brain injury (TBI) aims to maintain the normal cerebral perfusion in spite of the mass lesions that may occur (haematoma, contusion, and oedema). The monitoring of the intracranial pressure (ICP) is a step in that direction. The intra-parenchymal catheters have the lowest incidence of infection compared to intra-ventricular/subdural catheters with reliable and accurate pressure recordings. The major disadvantage of the intra-parenchymal catheters is the cost, especially in developing nations. Hypothesis: Resterilized intra-parenchymal strain gauge catheters can be used safely for ICP monitoring without any added risk of meningitis. The reusage of catheters can bring down the costs. Resterilized catheters/equipment have been approved for usage in cardiac usage, but such study on ICP catheters has not been carried out so far in any part of the world. Methodology: A total of 100 consecutive cases of severe TBI receiving ICP monitoring at a level 1 trauma center of a developing nation were prospectively studied (34 cases had fresh catheters, and 66 had resterilized [using ethylene oxide] catheters). Observations: The use of reused resterilized catheters was not associated with increased incidence of meningitis or fever (the surrogate marker for infection in this study). Also, there was concordance between the pressure recording of reused catheters and operative finding/subsequent computed tomography scans. These catheters after sterilization could be reused 2–4 times and reliably recorded the ICP (insignificant drift) with no increase in the incidence of meningitis. Conclusions: Usage of resterilized intra-parenchymal ICP catheters is feasible, safe, efficacious, and cost effective and brings down the cost of monitoring significantly.
Keywords: Intra-parenchymal intracranial pressure catheter; resterilized reused catheters; traumatic brain injuries